Anthelmintic effect of thymol and thymol acetate on sheep gastrointestinal nematodes and their toxicity in mice - André,Weibson Paz Pinheiro (2017)
Abstract Thymol is a monoterpene and acetylation form of this compound can reduce the toxicity and enhance its biological effects. The objective of this study was to evaluate the effect of thymol and thymol acetate (TA) on egg, larva and adult Haemonchus contortus and the cuticular changes, acute toxicity in mice and the efficacy on sheep gastrointestinal nematodes. In vitro tests results were analyzed by analysis of variance (ANOVA) and followed by comparison with Tukey test or Bonferroni. The efficacy of in vivo test was calculated by the BootStreet program. In the egg hatch test (EHT), thymol (0.5 mg/mL) and TA (4 mg/mL) inhibited larval hatching by 98% and 67.1%, respectively. Thymol and TA (8 mg/mL) inhibited 100% of larval development. Thymol and TA (800 µg/mL) reduced the motility of adult worms, by 100% and 83.4%, respectively. Thymol caused cuticular changes in adult worm teguments. In the acute toxicity test, the LD50 of thymol and TA were 1,350.9 mg/kg and 4,144.4 mg/kg, respectively. Thymol and TA reduced sheep egg count per gram of faeces (epg) by 59.8% and 76.2%, respectively. In in vitro tests thymol presented better anthelmintic activity than TA. However TA was less toxic and in in vivo test efficacy was similar.